Faktor-Faktor yang Mempengaruhi Work Life Balance Tenaga Kesehatan Di Rumah Sakit Pada Masa Pandemi Covid-19 - Edward Dian Suwito; Rian Adi Pamungkas; Ratna Indrawati (Jurnal Health Sains, 2022)
This study aims to analyze the relationship between individual factors, work stress, and work conflict partially and simultaneously with work life balance in government hospitals and private hospitals. This research uses explanatory causality quantitative analysis research method with SPSS quantitative method. Calculation of the sample using non purposive sampling as many as 200. The independent variables of this study are individual factors, work stress, and work conflict, while work life balance is the dependent variable. The study used a questionnaire as a research instrument with a 5-level Likert scale measurement. The data were analyzed by correlation analysis and regression through Multiple Linear Regression. The conclusion of this study shows that there is a negative and significant relationship between individual factors, work stress, and work conflict with work life balance in Government Hospitals and Private Hospitals, either partially or simultaneously. The suggestion from the researcher is that future researchers are expected to be able to analyze research related to work life balance and use the Structure Equation Model to see the direct and indirect effects of each predictor. In addition, the next research adds an intervening/mediation variable to find out further the effect on work life balance